Aplicación De Internet Y Su Influencia En El Desarrollo De Procesos Educativos Interactivos, En Los Estudiantes Y Tutores De Educación General Básica Superior De La Unidad Educativa A Distancia De Los Rìos, Extensiòn Babahoyo De Este Cantòn. - Real Zumba.Freddy (2015)
This thesis presents a research project on using the Internet on students and tutors of the Open University of Los Ríos, issues involving implementation and support processes interactive lessons to improve learning in semi modality. The author considers as a case study for Distance Education Unit Fiscomisional Los Rios, belonging to Canton Babahoyo, who despite having made available such Internet service not implemented .the problem itself is specified by the lack of Internet use in the processes of teaching and learning to generate interactive learning between the Guardians and Students, This is to determine the effect of the implementation of the Internet on development in learning between Guardians and Students. The main objective is that with the implementation of Internet interactive learning are improved teaching and learning processes. Achieving an optimal level of knowledge of tutors and students so they can interact using this technology.